Trend Komunikasi Politik di Media Sosial - Nurhidayat, Ipan; Garis, Regi Refian (JURNAL LANSKAP POLITIK, 2023)
Communication is an activity that cannot be separated from human life. Based on its form, there is interpersonal communication, small group communication, public communication, organizational communication and mass communication. Based on the context, there are several types of communication, such as business communication, health communication, intercultural communication, family communication and also political communication. Basically communication is a relationship between humans in order to achieve mutual understanding (mutual understanding). To explain about ganjar pranowo's political communication through Instagram social media, the author uses a descriptive method with a qualitative approach. With this method the researcher tries to describe, analyze, and build meaning about political communication in the current era. Ganjar Pranowo is a political figure who is very active on social media and often uses social media to communicate with his people. Ganjar Pranowo is well-known on social media for his accomplishments in advancing Central Java, and he also enjoys being involved in society both virtually and in person. The image of a politician must be effective and channeled to be effective. Social media is a popular media used and followed by many people. This has the potential to change public opinion in a number of ways. Ganjar Pranowo is a political figure who is very active on social media and often uses social media to communicate with his people.